Four new species of Talaromyces from clinical sources. Issue 10 (28th June 2017) - Guevara‐Suarez, Marcela; Sutton, Deanna A.; Gené, Josepa; García, Dania; Wiederhold, Nathan; Guarro, Josep; Cano‐Lira, José F.
Summary: The genus Talaromyces constitutes an important group of molds with species that are mainly found in soil, indoor environments and food products. Traditionally, it has been considered, together with Eupenicillium, the teleomorphic state of Penicillium . However, the taxonomy of these fungi has changed considerably, and Talaromyces currently includes sexually and asexually reproducing species. In a previous study of the occurrence of penicillium‐like fungi from clinical samples in the USA, we used the combined phylogeny of the internal transcribed spacer (ITS) region of the rDNA and β‐tubulin ( BenA ) gene to identify 31 isolates of Talaromyces, 85 of Penicillium and two of Rasamsonia . However, seven isolates of Talaromyces were assigned to the corresponding sections but not to any particular species. In this study, we have resolved the taxonomy of these isolates through a multilocus sequence analysis of the ITS, fragments of the BenA, calmodulin ( CaM ), and RNA polymerase II second largest subunit ( RPB2 ) genes, and a detailed phenotypic study. As a result, four new species are described and illustrated, ie Talaromyces alveolaris, T. georgiensis, T. minnesotensis and T. rapidus .